MANGATOON AS A MEDIUM FOR DEVELOPING ENGLISH READING SKILLS - Nurwahid Thayib pido; Rico Brianto; Dian Puspita Ramadhani (Jurnal Cakrawala Ilmiah, 2022)
This article introduces one method that can improve one's English language skills, namely the ability to read English. Given the important role of reading for the development of science, it is necessary to make efforts to improve students' reading skills, one of which is by utilizing English comics as a medium to improve English reading skills. Reading is one of the most important skills for us to master to improve our English language skills. Therefore, there are many methods out there that can develop reading skills. One of them is the media for reading comics using English. Mangatoon is an application that is much loved by teenagers who are very fond of reading comics. Many teenagers learn to read English from this application. This much-loved application is characterized by comic content that is presented very attractively. So that teenagers prefer to read comics through this application. Many teenagers think that with this application they can learn while developing the potential of their English skills. The author uses a qualitative method because this study wants to adjust the facts in the field by describing in detail the mangatoon application